ESTIMASI BESARAN SEDIMENTASI DI SUB DAS PAGUYAMAN YANG BERADA DI KABUPATEN GORONTALO - Adam, Eska Zuhriana; Rijal, Ahmad Syamsu; Tisen, Tisen; Matalapu, Irawan; Hendra, Hendra (Universitas Negeri Makassar, 2023)
Paguyaman watershed is the second largest watershed in Gorontalo province with an area of 3,485.65 which is a critical watershed. There is a problem of sedimentation in the watershed causing the river flow rate to slow down. It is hoped that it can be used as an alternative to overcome siltation. The research aims to estimate the amount of sedimentation and determine the spatial distribution of sedimentation in the Paguyaman sub-watershed, the method used is the Soil and Water Assessment Tool (SWAT) model. carried out with the help of geographic information systems (GIS) with ArcGIS 10.4 software, SWAT can describe hydrological processes (sedimentation). DEM data resolution (10x10) as the main input for the DAS delineation process. Soil data, land use, soil type, determines the land unit/hydrologic response unit (HRU) of the watershed. Rainfall and climate data (temperature, average humidity, solar intensity, wind speed) obtained from stations spread over the area are integrated into SWAT to calculate sedimentation. The results of the Paguyaman watershed have a very steep slope (> 40), land use is dominated by primary and secondary dryland forest with a total area of 49511.90 with a percentage of 45.39%, Tropudults soil type; Dystropepts area of 22125.96 with a percentage of 20.28%, DAS Paguyaman has 8202 HRU's and sub-basin 475 there are 5 classifications of sedimentation quantities, namely very high sedimentation 285.25 ha, with a percentage of 0.26%, high sedimentation 87.78 ha with a percentage of 0.08%, moderate sedimentation 505.94 ha with a percentage of 0.45%, low sedimentation 3040.37 ha a percentage of 2.79% and very low sedimentation 105171.27 ha with a percentage of 96.41%.